Numerical Study of Flat-top Piston Head Structure Under Different Materials - Hendry Sakke Tira; Muhammad Ponco Zulfikar; I Made Adi Sayoga (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2023)
Piston is an important component of two-wheeler since it is able to generate high pressure and convey combustion energy into crank rotation. Piston is typically made of aluminium alloy and other materials that can endure extremely high pressure and heat on the surface during combustion. Aluminium alloy and magnesium alloy are two distinctive materials that are frequently used in piston head. The objective of this study is to use numerical analysis to investigate and analyse a flat-top piston head made of two different materials. The design process allows usage Solidworks software, and the analysis process makes use of Ansys software. The Ansys simulation is intended for evaluating the maximum stress, total deformation variability, and safety factor for each material analysed. The findings from the analysis indicate that the deformation of the piston head made of aluminium alloy is smaller than that of magnesium. Whereas the aluminium alloy has a lower safety factor than magnesium. The von Mises stresses for the two materials, however, are essentially equal.